The Practice of Fish Trading Using the Mid-Sea Pickup System (Nyepai) in Kampung Laut Subdistrict: An Islamic Law Perspective - Firman Saputra; Haeran; Erwina Kartikadevi (Zabags Qu Publish, 2025)
This study examines the practice of fish trading conducted via the mid-sea pickup system (nyepai) in Kampung Laut Subdistrict, Tanjung Jabung Timur, from the perspective of Islamic law. Nyepai is a local trading arrangement in which buyers collect fishermen’s catches at sea prior to the vessels’ return to shore. The research aims to (1) describe the operational mechanisms of nyepai transactions and (2) evaluate their conformity with core Islamic sale principles such as clarity of the object, fairness, mutual consent, and the prohibition of gharar (excessive uncertainty). Employing a qualitative descriptive-analytic approach, data were gathered through semi-structured interviews, direct observation, and documentary review, and were analyzed through iterative data reduction, thematic presentation, and interpretive synthesis. Findings indicate that nyepai transactions are typically concluded verbally at sea, involve delayed physical delivery and payment, and rely heavily on interpersonal trust, factors that introduce varying degrees of transactional uncertainty. While some elements of nyepai may conflict with strict interpretations of Islamic contract principles, local mitigation practices (e.g., post-delivery inspection and compensation mechanisms) can reduce perceived unfairness and uncertainty. The study contributes empirical insights to contemporary fiqh of commercial transactions and offers a basis for developing contextually appropriate, sharia-compliant trading guidelines for coastal communities.